Peranan Organisasi Karang Taruna Dalam Pemberdayaan Masyarakat Desa (Suatu Studi Di Desa Tewasen, Desa Pondos, Desa Elusan, Desa Wakan Kecamatan Amurang Barat Kabupaten Minahasa Selatan) - Kawalod, Farra Aprilia; Rorong, Arie Junus; Londa, Very Yohanes (Sam Ratulangi University, 2015)
ABSTRACT : Observe to the problem that faced by young generation, it is necessary to attempt that will helpthose young generation to solve problems which that attempt need a place to develop and direct them. Theimplementation of development is a government duty from national to local government with appropriateexpertise. Then the implementation will translate to society life especially in counselling such as build anorganization that become a place to develop young generation in village. As an example is Karang Tarunathat can be a place to accommodating the aspirations and involved young generation to manage. Beside,Karang Taruna also play role as place to grow sense of nationality, develop self potency and social welfare.Research Method : This research using descriptive qualitative approaching method by deep interview to 7responden, observe and files investigation using additional instruments such as interview guidance list,recorder and stationery. Research results : According the role of Karang Taruna from 4 villages, they haven’timplemented the main role and duty as a organization yet. There were only two villages that have a goodimplementation , they are Tewasen and Pondos Village while the other two haven’t optimal implementationyet. Karang Taruna of Pondos Village has a good program’s plan but in their role as a government partner insociety welfare hasn’t optimal yet while good partnership shown is social life but need more guidance. Elusanand Wakan Village had not an optimal program’s plan, society empowerment and social welfare. Conclution :There are only two Karang Taruna with a good role implementation of society empowerment from fourKarang Taruna as an object of this research. They are Karang Taruna of Tewasen and Pondos Village whileKarang Taruna of Elusan and Wakan Village haven’t good implementation yet.Keywords : role, Karang Taruna Organization, village society.